Pretend play in children with a congenital visual impairment - Federici, Stefano; Bardin, Alessandra; Borsini, Camilla; Delvecchio, Elisa; Lepri, Alessandro; Morelli, Federica; Scognamillo, Ilaria; Cocchi, Elena; Santini, Luca; Signorini, Sabrina (Frontiers in Psychology, 2025)
BackgroundModern theories embrace a conception of pretend play as a behavior closely related to exploration, curiosity, and the affective domain, as well as problem solving and creative thinking. Although a widely studied construct, pretend play in children with a visual impairment has received little research attention.ObjectiveThis study examined the influence of congenital visual impairments on symbolic skills by comparing differences in pretend play between 31 children (aged 3–9 years) with moderate to severe visual impairment or blindness with typically developing peers.MethodsThe Affect in Play Scale was used as a measure of pretend play. A storytelling task, a parent-reported questionnaire, and the Emotion Regulation Checklist were used to examine the relationships between pretend play, creativity, and emotion regulation in both groups.ResultsResults indicated that typically developing children demonstrated higher pretend play skills than their blind and visually impaired peers (p < 0.001), but there was no correlation between severity of impairment and play skills. Storytelling skills also appeared to be impaired in the population of children with blindness/visual impairment (p < 0.05), suggesting a link between pretend play and creativity. The data also showed a trend of negative correlation between emotion dysregulation and pretend play and storytelling performance in the visually impaired group, emphasizing that greater dysregulation was associated with lower pretend play skills.ConclusionOur study has highlighted the importance of focusing a rehabilitation pathway on improving pretend play skills in the context of visual impairment to promote the development of the individual, supporting both cognitive and emotional dimensions.